Analisis Nilai-Nilai Pada Tradisi Tabut Di Kota Bengkulu - Ratna Wulan Sari; Agus Susilo (CV. Aksara Global, 2024)
This research aims to analyze the character values ​​in the Tabut ceremony tradition in Bengkulu City. The research method used is a descriptive method. Data collection techniques in this research used interview and documentation techniques. The data analysis technique used is the Miles and Huberman interactive data analysis model and interviews. The results of the research describe the values ​​contained in the Tabut tradition in Bengkulu which is oral literature which contains local wisdom values. The Tabut tradition is legendary, not only locally but internationally. The values ​​contained in the Tabut ceremony procession include community behavior such as mutual cooperation, concern for others, and mutual help. The religious value in the Ark procession contains the meaning that all humans are from the land and will return to the land and pray to Allah SWT. The values ​​and meanings contained in the Ark tradition continue to become oral literature that must be protected so that they are not lost and eroded by the progress of globalization. Today's young generation is more inclined towards increasingly sophisticated technological advances so that if the Ark tradition is not cultivated it will be neglected.